A study of corporate real estate as an instrument for corporate branding - Bell, Andrew (My University, 2016)
Purpose: The primary aim of this research is to establish an awareness of CRE as an instrument for branding and determine which aspects of CRE may contribute to and even strengthen the corporate branding of companies. Design/Methodology/Approach: Comprehensive literature review, together with a quantitative analysis of an in-depth questionnaire survey sent to owneroccupier companies and qualitative analysis of semi-structured interviews with industry professionals. Findings: Not all aspects of corporate real estate are equally important when considered in relation to corporate branding, furthermore the importance of these aspects vary between the different owner-occupier groups surveyed. Research limitations: this research was limited to a relatively small group of owner-occupier companies that occupy recently developed buildings in the primary office nodes in Johannesburg, South Africa. Practical implications: The primary objective is to aid corporate real estate managers and developers in better understanding how the strategic positioning and intrinsic aspects of CRE can influence the corporate brand of a company. Originality and value: This research identifies and ranks the different CRE aspects that could be utilised as part of a corporate branding strategy, no concluding evidence has been established as to how the identified aspects can be used as part of a corporate branding or corporate real estate strategy. Recommendations: Further research to establish how the identified corporate real estate aspects could potentially be implemented as part of a branding strategy or CREM strategy. Keywords: Real Estate, Branding, Strategy, CRE, CREM.
A research report submitted to the Faculty of Engineering and the Built Environment, of the University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the Master of Science in Building, Property Development and Management. Johannesburg, 2014
Keywords: Real property--South Africa; Real estate agents--South Africa; City planning--South Africa--Johannesburg